Shall We Tax the Risk Premium? - Dirk Schindler; Bodo Hilgers (University of Konstanz, Center of Finance and Econometrics (CoFE), 2002)
Should the realized risk premium be taxed – or not? In a simple two asset portfolio model we analyze the optimal taxation rule when the economy faces aggregate risk. We show in an appropriate designed tax system, that the risk premium of the risky asset should be fully taxed if the households are risk neutral in public consumption. If they are risk averse in public consumption, too, a positive tax rate below 100 % is optimal. We show further, that an efficient risk allocation between public and private consumption can be achieved without any distortion costs.
urn:nbn:de:bsz:352-opus-9473
Keywords: D10; H21; G11; 330; Risk-Taking; Risk Premium; Optimal Taxation; Aggregate Risk; Kapitalertragsteuer; Risikoprämie; Optimale Besteuerung; Gesamtwirtschaftlicher Konsum; Öffentlicher Konsum; Risiko; Theorie